Model Perencanaan Pembangunan Pedesaan Berbasis pada Sektor Pertanian (Studi Kasus Kecamatan Moyudan Kabupaten Sleman) - Lilik Sutiarso; Sigit Supadmo Arif; Murtiningrum Murtiningrum (agriTECH, 2005)
Sleman, as an area with rapid economic growth, againts the challenge of development in relation with population expansion, local autonomy and good governance. In one hand, there is lack of synergy among development stakeholders, on the other hand. information is ineffectively used during the decision making process. This paper aimed to develop a model of rural development plan based on agricultural sector using two computer softwares,(i) Geographical Information System (GIS) as spasial information system and (ii) Powersim to program the dynamic system behaviour. The model provides information on existing condition and consists of five components namely geography, development function, infrastructure, institution, and data catalog. The model was developed through formulating causal diagrams of development sectors and set it in a dynamic programming. The model was then validated in Moyudan, Sleman for the case of agriculture development, which is showed that the model was valid.